Force prediction in ultrasonic vibration-assisted milling. Issue 2 (16th September 2020) - Feng, Yixuan; Hsu, Fu-Chuan; Lu, Yu-Ting; Lin, Yu-Fu; Lin, Chorng-Tyan; Lin, Chiu-Feng; Lu, Ying-Cheng; Liang, Steven Y.
Abstract: The use of ultrasonic vibration on milling has several benefits including reduction of the machining forces. However, the mechanism behind this phenomenon is unclear, and reported analytical studies are quite limited. An analytical predictive modeling work is presented in the current study. To describe the intermittent contact between tool and workpiece due to vibration, conditions of tool-workpiece separation are described by three types of criteria. The first criterion checks the instantaneous moving direction of cutting edge. The second criterion examines the radial displacement of cutting edge under vibration. The third criterion considers the smaller chip thickness due to extra displacement from previous tool path. If the material is being removed, the force prediction is performed through transformation of milling configuration, calculation of shear flow stress by mechanics of machining, and calculation of feed, cutting and axial force after coordinate transformation. The predicted forces are compared with experimental measurements on Aluminum alloy 2A12 for validation. The average percentage difference is 13.6% in feed direction and 13.8% in cutting direction. This is the first approach to mathematically describe the intermittent contact between tool and workpiece and combine the kinematic analysis with mechanics of machining to predict cutting forces.